Performance of crossbred cattle and comparison of sires evaluation methods under organized farm condition - SAHANA, G; GURNANAI, M (The Indian Journal of Animal Sciences, 2013)
The efficiency of sire evaluation methods in organized head with small progeny group size was examined along with performance evaluation of crossbred cattle. The data on 1 224 first lactation performance records of Karan Fries (Holstein Freisian x zedu) cows born out of 129 sires and spread over 21 years were used to examine the efficiency, accurcy and repeaatability of 5 sire evaluation methods, Viz. simple daughter average index (I), contemporary comparison method (CC), least squares method (LSQ), simplified regressed least squares method (SRLS) and best linear unbiased prediction (BLUP). The least squares of variance showed that genetic group had highly significant (P<0.01) effect ib age at first calving (AFC), first lactation 305-day or less milk yield (305MY) and first lactation total milk yield (LTMY). The season of calving had highly significant effect on 305MY, LTMY, first service period (FSP)and first calving interval (FCI). The period of calving had highly significant effect on 305MY, FSP, and FCI. The CC method was observed to be the most efficient sire evaluation method and I the least efficient. The F1 (HF X Tharparkar) crosses had highest 305 MY among all the genetic groups. The rank correlations of CC method with other 4 methods ranged between 0.77 with SRLS and 0.85 with BLUP. The repeatability of sires’ breeding value estimation in CC, LSQ, SRLS and BLUP was lower with less number of progeny record (5-8), however, increased with the increase of progeny group size.